Vulnerability, risk and protection factors in children and adolescents victims of sexual abuse in North Lima - Torres Villavicencio, Miguel Ángel (2021)
Antecedents: It is analyzed, from the forensic psychological perspective, the sociodemographic factors and characteristics of sexual abuse. To do this, vulnerability, risk and protection factors are identified. Objectives: To evaluate the vulnerability, risk and protection factors in boys, girls and adolescents victims of sexual abuse in North Lima. Method: This research is basic, transectional, descriptive level, not experimental. The unit of analysis is made up of boys, girls and adolescents who are victims of sexual abuse, aged between 3 and 18 years. The source of analysis is 55 expert reports of these victims treated in a forensic psychology service in North Lima. Four factor verification instruments were used: sociodemographic-sexual abuse, vulnerability, risk and protection; validated according to expert judgment and reliability by Cronbach's alpha. Results: Most of the victims are registered as female adolescents, coming from nuclear families: 20%, migrants living in poverty and extreme poverty; 96.4% abused under threat. In addition, high percentages of vulnerability factors were found in previous victimizations and in psychological disorders. Conclusions: The highest percentages of risk are found in interfamily relationships and in terms of protective factors, there is a low level of social skills.